2000
DOI: 10.1098/rspb.2000.1139
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachiainfection frequencies in insects: evidence of a global equilibrium?

Abstract: Wolbachia are a group of cytoplasmically inherited bacteria that cause reproduction alterations in arthropods, including parthenogenesis, reproductive incompatibility, feminization of genetic males and male killing. Previous general surveys of insects in Panama and Britain found Wolbachia to be common, occurring in 16^22% of species. Here, using similar polymerase chain reaction methods, we report that 19.3% of a sample of temperate North American insects are infected with Wolbachia, a frequency strikingly sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
665
4
16

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 727 publications
(704 citation statements)
references
References 34 publications
(64 reference statements)
19
665
4
16
Order By: Relevance
“…In insects, Wolbachia is a widespread and common endosymbiont. PCR-based screenings have shown that 16% of a large sample of neotropical insects are Wolbachia infected (Werren et al, 1995a), and similar figures have been found in a sample of palearctic (West et al, 1998) and nearctic insects (Werren and Windsor, 2000). Using an ultra-sensitive assay, figures up to 76% have been obtained for nearctic arthropods (Jeyaprakash and Hoy, 2000).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In insects, Wolbachia is a widespread and common endosymbiont. PCR-based screenings have shown that 16% of a large sample of neotropical insects are Wolbachia infected (Werren et al, 1995a), and similar figures have been found in a sample of palearctic (West et al, 1998) and nearctic insects (Werren and Windsor, 2000). Using an ultra-sensitive assay, figures up to 76% have been obtained for nearctic arthropods (Jeyaprakash and Hoy, 2000).…”
Section: Introductionmentioning
confidence: 70%
“…Sequences generated in this study are indicated in bold. The bar represents a distance of 0.050 (about 25 MY if a wsp evolutionary rate of 0.2% per MY is assumed, Wenseleers et al, 2001). and Solignac, 1995;Wenseleers et al, 1998;Werren et al, 1995a, b;Werren and Windsor, 2000) or more rarely, triple infections (Kondo et al, 2002;Vavre et al, 1999). A stable triple Wolbachia infection has also been created artificially by microinjection of an additional strain in double infected Drosophila (Rousset et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The first PCR was performed using the general eubacterial primer 27F (Lane, 1991) combined with 16SWolbR3; PCR conditions were as above. One microlitre of the first PCR was diluted 1/10 in water, and then used as a template in a second PCR, performed using internal primers W-EF and W-ER (Werren and Windsor, 2000), whose target sites are conserved in supergroups E-F. PCR conditions with these primers were as described in Werren and Windsor (2000). On the negative specimens, we also performed PCR with primers 16SWolbF and 16SWolbR3 under different conditions.…”
Section: Pcr Screening For W Pipientis: Primers and Pcr Conditionsmentioning
confidence: 99%
“…Those surveys appear to only include the winged stages of some aquatic insects found in terrestrial areas, sampled haphazardly as part of broader surveys focused on terrestrial arthropods. Other studies have tested members of the order Odonata and aquatic Coleoptera (Sontowski, Bernhard, Bleidorn, Schlegel, & Gerth, 2015; Thipaksorn, Jamnongluk, & Kittayapong, 2003), but very few studies have investigated other major aquatic taxa such as Ephemeroptera, Trichoptera, and Plecoptera (but see Werren & Windsor, 2000; Prakash & Puttaraju, 2007; Yun et al., 2014). These types of surveys are important to understand the global infection frequency of Wolbachia so that future research on the potential impact of these bacteria on arthropod populations can be assessed.…”
Section: Introductionmentioning
confidence: 99%